2008
DOI: 10.1177/0148607108319808
|View full text |Cite
|
Sign up to set email alerts
|

Impact of High‐Dose Antioxidants on Outcomes in Acutely Injured Patients

Abstract: A high-dose antioxidant protocol resulted in a 28% relative risk reduction in mortality and a significant reduction in both hospital and ICU length of stay. This protocol represents an inexpensive intervention to reduce mortality/morbidity in the trauma patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0
4

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(53 citation statements)
references
References 28 publications
2
47
0
4
Order By: Relevance
“…This approximates the minimal dose of parenteral ascorbate (1000 mg ascorbate/day) that raises the plasma ascorbate concentration of septic patients into the range of normal plasma levels (35). The dose should be tolerated well, judging from clinical trials that injected 1000-2000 mg ascorbate every 8-24 h for up to 7 days in critically ill surgical or acutely injured patients (5,11,16,39).…”
Section: Vitamin C Dosage and Safetymentioning
confidence: 99%
“…This approximates the minimal dose of parenteral ascorbate (1000 mg ascorbate/day) that raises the plasma ascorbate concentration of septic patients into the range of normal plasma levels (35). The dose should be tolerated well, judging from clinical trials that injected 1000-2000 mg ascorbate every 8-24 h for up to 7 days in critically ill surgical or acutely injured patients (5,11,16,39).…”
Section: Vitamin C Dosage and Safetymentioning
confidence: 99%
“…An association has been proposed between increased oxidative stress and poor outcomes in the critically ill, suggesting a potential role for antioxidant strategies in the intensive care unit (ICU) (3). Limiting levels of oxidative stress may prevent cellular death, decrease inflammation and reduce morbidity and mortality rates (4); therefore, the antioxidant properties of sedative drugs should be taken into consideration as an important part of ICU remedy strategies, particularly when mechanical ventilation is required.…”
Section: Introductionmentioning
confidence: 99%
“…Recently a large, retrospective review was reported of adults with trauma before and after the initiation of protocolized administration of an antioxidant cocktail containing ascorbic acid, -tocopherol and selenium to all acutely injured patients [24]. Patients who were admitted after the implementation of the antioxidant protocol had improved outcomes including hospital mortality, length of ICU stay and length of hospital stay, with the most significant improvements noted in the sickest patients with a probability of survival <50% [24].…”
Section: Anti-oxidant Treatment Regimens Containing Seleniummentioning
confidence: 99%